2012
DOI: 10.4073/csr.2012.13
|View full text |Cite
|
Sign up to set email alerts
|

Interview and interrogation methods and their effects on true and false confessions

Abstract: The Campbell Collaboration (C2) was founded on the principle that systematic reviews on the effects of interventions will inform and help improve policy and services. C2 offers editorial and methodological support to review authors throughout the process of producing a systematic review. A number of C2's editors, librarians, methodologists and external peerreviewers contribute.The Campbell Collaboration ABSTRACT 6

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
129
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 94 publications
(137 citation statements)
references
References 74 publications
3
129
1
1
Order By: Relevance
“…The reason may be in their promotion in the Slovenian interrogation manual. It would appear that the manual needs revision, cautioning its readers about the dangers of using those interrogation techniques that have been argued as ones that can significantly increase the risk of false confessions (Meissner et al, 2012). Police interrogations have been the subject of a growing body of scientific research.…”
Section: Resultsmentioning
confidence: 99%
“…The reason may be in their promotion in the Slovenian interrogation manual. It would appear that the manual needs revision, cautioning its readers about the dangers of using those interrogation techniques that have been argued as ones that can significantly increase the risk of false confessions (Meissner et al, 2012). Police interrogations have been the subject of a growing body of scientific research.…”
Section: Resultsmentioning
confidence: 99%
“…The studies that have examined rapport in interrogations have done so by comparing the effectiveness of different interrogation approaches (e.g., informational-gathering v. accusatorial). These studies have examined how clusters of techniques influence investigative outcomes (Bull & Soukara, 2010;Meissner et al, 2012;Walsh & Bull, 2012). For example, a recent meta analysis found that the information-gathering approach, generally characterized by a non-confrontational interviewer who builds…”
Section: Discussionmentioning
confidence: 99%
“…At the end of the interrogation, the police investigator asks the suspect for a confession, and a detailed account of what happened (Kassin & Gudjonsson, 2004;Meissner, Russano, & Narchet, 2010). Research demonstrates that this confrontational and accusatorial approach to interrogations may successfully elicit confessions from the guilty but also puts innocent suspects at risk of confessing to a crime they did not commit (see Kassin et al, 2010;Meissner, Redlich, Bhatt, & Brandon, 2012).…”
Section: Background and Significancementioning
confidence: 99%
“…The aim of the present study is to investigate expectancy effects on behaviour when expectancies have only been implied through information about the participant's group membership. Given that most research on investigative interviews has used accusatory or confession driven interview techniques to study interviewee behaviour (see Kassin et al, 2009;Meissner, Redlich, Bhatt, & Brandon, 2012), little is known about expectancy confirmation effects in non-accusatory environments while using information-gathering techniques. Additionally, inducing expectancy effects as a stereotype has not been investigated in a forensic setting using non-racially motivated false beliefs.…”
Section: Present Studymentioning
confidence: 99%